2016
DOI: 10.5935/abc.20160139
|View full text |Cite
|
Sign up to set email alerts
|

Fragmented QRS for Risk Stratification in Patients Undergoing First Diagnostic Coronary Angiography

Abstract: BackgroundOnly a small proportion of patients referred for coronary angiography with suspected coronary artery disease (CAD) have the diagnosis of obstructive CAD confirmed by the exam. For this reason, further strategies for risk stratification are necessary.ObjectiveTo investigate the relationship of the presence of fragmented QRS (fQRS) on admission electrocardiogram with angiographically detected CAD and CAD severity in patients without known vascular diseases and myocardial fibrosis, undergoing first diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 21 publications
2
9
0
1
Order By: Relevance
“…[ 4 , 9 , 22 ] In patients with LD, most left ventricular myocardial are supplied by the poster lateral branches and posterior descending artery originating from the left circumflex artery. [ 23 ] In contrast, the IVS is supplied by the posterior descending branch of the RCA in individuals with RD. Additionally, the IVS is shared by the RCA and left circumflex artery in CD.…”
Section: Discussionmentioning
confidence: 99%
“…[ 4 , 9 , 22 ] In patients with LD, most left ventricular myocardial are supplied by the poster lateral branches and posterior descending artery originating from the left circumflex artery. [ 23 ] In contrast, the IVS is supplied by the posterior descending branch of the RCA in individuals with RD. Additionally, the IVS is shared by the RCA and left circumflex artery in CD.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented QRS is a novel ECG parameter that is used quite often in daily practice and that is gaining importance. 23 However, the number of fQRS derivations has recently attracted a greater interest. Even though there is no study showing the importance of the presence of fQRS in a single lead, the clinical significance of QRS distortion in only one lead, which is another important ECG finding in acute STEMI, 24 was investigated in a recently published study.…”
Section: Discussionmentioning
confidence: 99%
“…One study by Eyuboglu M showed the frequency of f QRS as 23.5% 4 in NSTEMI patients versus another study by Min Li showing the frequency of 55.56%. 2 But no published study available in local setting to tell us about the prevalence of this finding in our local population.…”
Section: Introductionmentioning
confidence: 95%
“…4 fQRS complexes are a new ECG indicator, which shows delay in conduction of electrical current in coronary artery disease patients. [2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19] One study found that 23.5% cases of NSTEMI patients had f QRS. 3 But another study revealed that fQRS complex was seen in 66.5% cases of NSTEMI.…”
Section: Wwwtheprofesionalcom 64mentioning
confidence: 99%